Supply chain management and logistics in Latin America : a multi-country perspective : selected papers from the 2016 MIT Scale Latin American Conference on Logistics and Supply Chain Management, 21-22 March 2016, Cambridge MA - Yoshizaki, Hugo; Martínez, Josué C. Velázquez; Argueta, Christopher Mejía (Emerald Publishing, 2019)
Latin America is a fast-growing market, but its poor infrastructure, explosive urbanization, expensive and inefficient logistics, and multiple social problems continue to pose major problems to logistics professionals and academics. Here leading scholars across Brazil, Colombia, Cuba, Ecuador, Peru, Panama, and the USA address these issues.